When Deception Promotes Dignity: The Ethics of Using Illusion to Create Safe Spaces for Persons Living with Dementia - Locke Teti, Stowe; Deemer, David A.; Hercules, William J.; Anderson, Diana C. (The International Journal of Whole Person Care, 2025)
Caring for persons living with dementia (PLWD) is challenging. Some of the most challenging aspects include managing behavioral and psychologic symptoms of dementia (BPSD). Many patients and families will consider dementia care facilities to better manage BPSD, which can contain design elements that use the physical environment to decrease BPSD by deceiving residents and controlling their behavior—all for their own benefit and safety. This immersive approach to behavior management represents a more holistic way to manage BPSD. Considering the especially vulnerable status of PLWD, these design elements should be thoughtfully implemented, researched post-implementation, and discussed with patients and their loved ones. The design-based approach to managing BPSD demonstrates the obligation healthcare providers and facility designers have to be more holistic in designing care environments for PLWD, especially for those living in dementia care facilities.